REPRESENTASI KELAS SOSIAL DALAM FILM GUNDALA (ANALISIS SEMIOTIKA MODEL PEIRCE) - Bimantara, Iskandar (The Commercium, 2021)
This study aimed to discuss about social class representative on Gundala movie. Several scenes were taken in showing how social class formed and lived by the main character named Sancaka who lived a life on the street and grew as a security unit. This study used qualitative descriptive method by using analysis unit in the form of text and picture appeared as a form of social class representative. The researcher used semiotic theory by Charles Sanders Peirce as analysis and divide it into three forms: Icon, Index, Symbol by using semiotic process. The result shows the division of social class is obvious, happened intentionally, created class struggle, class antagonism, and became one of conflict point in society.